How land allocation and technology innovation affect the sustainability of agriculture in Argentina Pampas: an expanded life cycle analysis - Rotolo, Gloria Claudia; Montico, Sergio; Francis, C.A.; Ulgiati, Sergio (2018)
Pampas region grows more than 80% of Argentina's main crops, with maize (Zea maiz L.), soybean (Glycine max L. Merr.) and wheat (Triticum aestivum L.) producing crop and landscape homogeneity that reduces biodiversity, agricultural system resilience and current and future regional welfare. With growing population and markets, there is a call for new agricultural patterns to meet increased food demand, together with concern for reducing environmental impact and improving social welfare. These challenges need rigorous approaches to measuring technological change costs and benefits as well as evaluating environmental impact of farmers' management practices. The objectives of this study are: [1] to evaluate resource use and environmental impact of current agricultural patterns in the northern part of Pampas region, [2] to contrast this with agricultural systems of previous decades, and [3] to analyze the incidence on space and time scales of the different proportions of land allocated to these three crops. Life cycle evaluations of cropping systems enlarge the scope of the analysis and help identify how problems might be solved. We utilize the SUMMA (SUstainability Multimethod Multiscale Assessment) framework for assessing the performance of integrated crop production in the northern Pampas in the years 1986–87, 1995–96, and 2009–10 based on actual land use data, compared to current systems with similar proportions of land distribution for the three crops, and to a wheat/soybean annual system. We also simulate other potential alternative land distribution scenarios. Results indicate a worsening of 9 to 12 out of 15 environmental indicators per unit of area (density of impacts), while there is an improvement per unit of product or income. The grain yield accounted in energy per hectare increased three times in relation to the year of reference (1986), while the energy demand decreased by 32%, blue water demand increased 50%. Acidification increased more than twice (7.99 kg SO2 eq./ha), while carbon emissions (982 kg CO2 eq./ha in 2009) decreased. These results provide a benchmark for further studies where new alternatives of crop distribution may prove environmentally and economically desirable choices for farmers in the Pampas.